Geometry of Ricci and $(η,ω)$-Ricci solitons on the Sasaki–Kenmotsu manifold - Sangeetha, M.; Nagaraja, H. G. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 514.7We characterize the Sasaki–Kenmotsu manifold by using different kinds of solitons. Thus, we introduce a new type of solitons on the Sasaki–Kenmotsu manifold using a bicontact structure. First, we observe the properties of the Ricci soliton on $(η,ω)$-Sasaki–Kenmotsu manifold by using bicontact structure. Then we extended the $η$-Ricci soliton as an $(η,ω)$-Ricci soliton and a conformal $η$-Ricci soliton as a conformal $(η,ω)$-Ricci soliton by using the bicontact structure.